China's Changing Alcohol Market and Need for an Enhanced Policy Response: A Narrative Review - Liu S; Huang F; Zhu X; Zhou S; Si X; Zhao Y; Liu Y; Zhang X; Casswell S (MDPI (Basel, Switzerland), 2022)
This study describes trends in alcohol consumption in the context of an expanding commercial context, current policy responses, and flaws in relation to international best practice for alcohol control in China. We surveyed the literature and other documents in Chinese or English up to December 2020 on policy responses to alcohol consumption and harm, industry structure, and marketing practices in China. Databases searched included PubMed, China National Knowledge Internet, Wanfang Data, Web of Science, and Baidu Scholar. We also scanned the official websites of government organizations and gathered information using snowballing. We analyzed existing alcohol policy against evidence-based, cost-effective policies for reducing alcohol harm. Our findings show that although some restrictive policies have been enacted with potential impacts on alcohol harm, they are not comprehensive, and some are poorly executed. The long history of alcohol use remains an important element in alcohol consumption by the Chinese population. However, alcohol marketing and promotion, ease of access, and affordability have become increasingly prominent. The gaps identified in alcohol policy suggest improved strategies and measures to reduce the harmful use of alcohol are urgently needed in China.
This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https:// creativecommons.org/licenses/by/ 4.0/).
Keywords: China; affordability; alcohol; consumption; industry; marketing; policy response; Alcohol Drinking; China; Costs and Cost Analysis; Marketing; Public Policy